2022
DOI: 10.1037/xhp0001012
|View full text |Cite
|
Sign up to set email alerts
|

Fixation, flexibility, and creativity: The dynamics of mind wandering.

Abstract: The mind-wandering literature is long on results and short on theory. One notable exception is the Dynamic Framework, a theoretical framework that characterizes mind wandering as thoughts that are relatively unconstrained from deliberate and automatic sources, or “freely moving.” Critically, this framework makes numerous testable predictions, including (a) a positive association between freely moving thought and ADHD, (b) negative associations between freely moving thought and depression, anxiety, and OCD, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 66 publications
3
36
2
Order By: Relevance
“…Even though it is not clear whether the mind game , the matrices task [18,42] and the die-under-the-cup paradigm [18,43,44] differ in their difficulty of justifying dishonest behaviour, we judge these setups to be largely similar, so we do not assume that this methodological difference drives the divergence of results across studies. Moreover, as recently shown, the relation of cognitive flexibility and creativity is quite ambiguous [45] and creativity does not seem to be exclusively related to the generation of unethical justifications but to the production of justifications in general [46]. Speculatively, creative thinking might lead to more ethical justifications for some participants, thus promoting honesty, while other participants might come up with more unethical justifications, therefore opting for dishonest behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it is not clear whether the mind game , the matrices task [18,42] and the die-under-the-cup paradigm [18,43,44] differ in their difficulty of justifying dishonest behaviour, we judge these setups to be largely similar, so we do not assume that this methodological difference drives the divergence of results across studies. Moreover, as recently shown, the relation of cognitive flexibility and creativity is quite ambiguous [45] and creativity does not seem to be exclusively related to the generation of unethical justifications but to the production of justifications in general [46]. Speculatively, creative thinking might lead to more ethical justifications for some participants, thus promoting honesty, while other participants might come up with more unethical justifications, therefore opting for dishonest behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…6Recent research may also support our hypothesis that creative incubation benefits from moderate levels of constraint. Smith et al (2022) found a U-shaped relationship between freely moving thought and creative incubation during a 0-back task. Specifically, moderate ratings of freely moving thought were associated with heightened creativity, compared with low and high ratings.…”
mentioning
confidence: 95%
“…Some studies have shown that the degree of social isolation during the COVID-19 pandemic is associated with depression ( 28 ). We found that a dynamic model of mind wandering can predict depression, while interventions for mind wandering have been shown to alleviate depression symptoms ( 29 ).…”
Section: Introductionmentioning
confidence: 99%